Transition of agricultural income sources in rural economies of Mexico - López-Santiago, Andrés; Hernández-Ortiz, Juan; Valdivia-Alcalá, Ramón; López-Santiago, Marco (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Traditionally, agriculture has been the main economic activity of rural communities, however, there are other sources of income that contribute to expenditures on family well-being. Nevertheless, the dynamics of these flows are unknown due to the absence of official statistics for small populations, which makes it difficult to analyze them in relation to poverty. Through an econometric model, the objective was to analyze the transition of income from agricultural production to sources in the service sector and remittances. It was taken as a study case, "Eleodoro Dávila" town from Filomeno Mata municipality, Veracruz, Mexico. Randomly, a questionnaire was applied to 33.33% of the population and an econometric model of expenditures on family well-being was built with data obtained. The dependent variable was expenditures on family well-being, while the independent variables were the diversity of sources of income. In addition, the elasticities of the independent variables were estimated from the econometric model. Primary and secondary activities, subsidies and household transfers were found to contribute to family well-being. In addition, it was found that a 1% increase in income from livestock production generates a 0.05% change in spending on family well-being, while agricultural production generates 0.16%. Trade, international and national remittances generate the greatest effects with 0.81%, 0.71% and 0.48% respectively. The situation that prevailed during 2019-2020 in the study community allows us to conclude that the agricultural sector has lost preponderance as the main source of income.